Assessment of Immunohistochemical Expression of Programmed Cell Death Ligand-1 in Invasive Urothelial Carcinoma - Rawat, Aakanksha; Gupta, Monika; Pawar, Devendra Singh; Singh, Sunita; Kumari, Sujata (Annals of Pathology and Laboratory Medicine, 2024)
Background: Infiltrating urothelial carcinoma is the most common histological variant (23.1%). This study was conducted to evaluate the immunohistochemical expression of PD-L1 in invasive urothelial carcinoma and to correlate PD-L1 expression with demographic data and the histological grade of urothelial carcinoma. Methods: The study comprised a total of 65 cases of muscle-invasive urothelial carcinoma collected over a period of one year and evaluated for PD-L1 expression using the immunohistochemistry technique. Results: Infiltrating urothelial carcinoma was the most common histological variant (23.1%), followed by poorly differentiated carcinoma (16.9%). PD-L1 positivity was observed in 47.7% of the total cases, while the remaining 52.3% showed no expression of PD-L1. Among the various histologic variants, poorly differentiated carcinoma (57.1%) was the largest group with weak expression of PD-L1; infiltrating urothelial carcinoma (26.7%) was the largest group with moderate expression of PD-L1, while the lymphoepithelioma-like variant (66.7%) was the largest group with strong expression of PD-L1. Our study was in concordance with other studies, showing that PD-L1 expression is not associated with clinicopathologic features like age, gender, and smoking status. Conclusion: The present study shows a significant difference between the various groups in terms of the distribution of histologic variants and PD-L1 positivity according to the WHO classification (2016) as well as severity scoring by the IHC technique.